STUDY REGARDING THE INFLUENCE OF CORROSIVE AGENTS ON THE SURFACE OF METALLIC MATERIAL LIKE STEEL - OLGA POPA; ANDREI-VLAD CIUBOTARIU; COSMIN CONSTANTIN GRIGORAȘ; ANA-MARIA ROȘU; VALENTIN ZICHIL (Journal of Engineering Studies and Research, 2022)
Corrosion is a process that involves the action of different agents on material surfaces. Corrosive agents in corrosion field can be ambient, saline and microbiological mediums. These agents can influence the mechanical properties of metallic material like steel. The aim of this research is to present the mechanic properties of sheet steel submitted at the action of corrosive agents. The metallic samples were analyzed in order to determinate the resistance at corrosion by stress-strain curves, deformation limit curves and (Atomic Force microscopy) AFM images. Relative results are obtained in the case of saline medium corrosion, meaning that the saline medium corrosion influences the metallic sample, in proportion to the degree of salinity. Also, the AFM images and topographies of metallic surface confirm this conclusion.